Identification of novel influenza A virus exposures by an improved high‐throughput multiplex MAGPIX platform and serum adsorption. Issue 2 (8th November 2019) - Li, Zhu‐Nan; Cheng, Emily; Poirot, Eugenie; Weber, Kimberly M.; Carney, Paul; Chang, Jessie; Liu, Feng; Gross, F. Liaini; Holiday, Crystal; Fry, Alicia; Stevens, James; Tumpey, Terrence; et al.
Abstract: Background: The development of serologic assays that can rapidly assess human exposure to novel influenza viruses remains a public health need. Previously, we developed an 11‐plex magnetic fluorescence microsphere immunoassay (MAGPIX) by using globular head domain recombinant hemagglutinins (rHAs) with serum adsorption using two ectodomain rHAs. Methods: We compared sera collected from two cohorts with novel influenza exposures: animal shelter staff during an A(H7N2) outbreak in New York City in 2016‐2017 (n = 119 single sera) and poultry workers from a live bird market in Bangladesh in 2012‐2014 (n = 29 pairs). Sera were analyzed by microneutralization (MN) assay and a 20‐plex MAGPIX assay with rHAs from 19 influenza strains (11 subtypes) combined with serum adsorption using 8 rHAs from A(H1N1) and A(H3N2) viruses. Antibody responses were analyzed to determine the novel influenza virus exposure. Results: Among persons with novel influenza virus exposures, the median fluorescence intensity (MFI) against the novel rHA from exposed influenza virus had the highest correlation with MN titers to the same viruses and could be confirmed by removal of cross‐reactivity from seasonal H1/H3 rHAs following serum adsorption. Interestingly, in persons with exposures to novel influenza viruses, age and MFIs against exposed novel HA were negatively correlated, whereas in persons without exposure to novel influenza viruses, age and MFI against novel HAs were positively correlated. Conclusions: This 20‐plex high‐throughput assay with serum adsorption will be a useful tool to detect novel influenza virus infections during influenza outbreak investigations and surveillance, especially when well‐paired serum samples are not available.